Sex Differences in the Effect of Resveratrol on DSS-Induced Colitis in Mice. (29th March 2017) - Wagnerova, Alexandra; Babickova, Janka; Liptak, Robert; Vlkova, Barbora; Celec, Peter; Gardlik, Roman
Abstract : Resveratrol is a natural polyphenol studied for its possible protective properties in inflammatory bowel diseases. Moreover, it has been shown to interact with estrogen receptors. In the present study, we aimed to investigate possible diverse effects of resveratrol on female and male mice in DSS-induced colitis. Thirty-seven C57BL/6 mice (21 female and 16 male) were divided into three groups for each sex. The first group received pure water (CTRL). The other two groups received 1.5% dextran sulfate sodium (DSS) to induce colitis from which one group was treated with resveratrol (DSS + RSV). Intake of 1.5% DSS caused weight loss in all DSS groups compared to control mice. Weight loss, stool consistency, and discomfort did not show any protective effect of resveratrol in males and showed even adverse effects in females. In females, the activity of myeloperoxidase was lower compared to that in males. However, colon length and spleen weight showed no sex differences, which can indicate the induction of only mild colitis in mice. Resveratrol did not have any effect on TNF-alpha levels. Taken together, these results for the first time propose possible diverse effects of resveratrol in DSS-induced colitis model depending on the sex of the animal. However, this conclusion must be confirmed by further analyses.